Analisis Ancaman Penyelundupan Uang (Bulk-cash Smuggling) dengan Metode SWOT - Andita Anton Subrata; Judijanto Judijanto; Christian Lumban Tobing (UJoST- Universal Journal of Science and Technology, 2023)
- Bulk-cash smuggling is the act of hiding a currency or monetary instrument with the intent to circumvent reporting requirements, through the transportation, transfer, or attempted transportation or transfer of currency or monetary instruments from one country to another. According to Law Number 8 of 2010 concerning the Prevention and Eradication of Money Laundering, it is stated that money smuggling is one part of money laundering crimes. In its development, cash smuggling, which was originally a stage of money laundering activities, has now become a form of transnational crime. Criminals generally use transportation media such as commercial and private aircraft, ships and transport vehicles and pedestrians to cross borders between countries. This research uses a qualitative method approach with SWOT analysis tools. Data collection comes from literature studies in the form of books, journals and other sources of information. The results showed that to overcome the problem of money smuggling can be done through efforts: increasing the presence of defense equipment of each stakeholder in border areas, increasing the degree of operation of each stakeholder independently and integrated to prevent money smuggling crimes and increasing the ability and professionalism of security forces in facing the threat of money smuggling.